2019
DOI: 10.1177/2050312119832090
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the impact of neurologic complications in patients with cirrhosis

Abstract: Patients with cirrhosis may experience neurologic complications, including hepatic encephalopathy. Hepatic encephalopathy may be classified as covert (mild symptoms (e.g. lack of awareness)) or overt (moderate to severe symptoms (e.g. confusion or coma)), and symptoms may overlap with other neurologic conditions (e.g. epilepsy, stroke). Managing hepatic encephalopathy includes identifying and treating precipitating factors (e.g. dehydration). First-line treatment for patients with overt hepatic encephalopathy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Alcoholic cirrhosis is more likely to cause epilepsy[ 4 , 10 ]. There may be several reasons for this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcoholic cirrhosis is more likely to cause epilepsy[ 4 , 10 ]. There may be several reasons for this.…”
Section: Discussionmentioning
confidence: 99%
“…Although not all manifestations are reversible by LT[ 1 ], it remains the final option for HE. Some reports suggest that damage to the central nervous system is reversible when elevated blood ammonia concentration does not exceed 200-400 mg/dL[ 26 ], and continuous improvement in cognition has been observed during the first year post-LT[ 10 ]. It has been also reported that 10% of patients present with seizures post-LT[ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Between 33 and 50% of patients with liver cirrhosis can develop minimal hepatic encephalopathy (MHE), the earliest form of hepatic encephalopathy (HE) 1 4 , which affects several million patients around the world 5 . MHE is characterized by mild cognitive impairment, alterations in attention 4 , 6 , 7 , psychomotor slowing and impaired motor coordination 7 , 8 , altered postural control 9 associated with increased risk of falls 10 , and impaired fitness to drive 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%